PbSe Quantum Dot Passivated Via Mixed Halide Perovskite Nanocrystals for Solar Cells With Over 9% Efficiency. Issue 12 (6th November 2018) - Hu, Long; Zhang, Zhilong; Patterson, Robert J.; Shivarudraiah, Sunil B.; Zhou, Zhicong; Ng, Michael; Huang, Shujuang; Halpert, Jonathan E.
Abstract : PbSe quantum dots (QDs) have stronger electronic coupling resulting from a large Bohr exciton radius, suggesting PbSe QDs may be able to achieve superior charge separation and transport in optoelectronic devices compared with PbS QDs. However, PbS QDs solar cell have achieved a certified 12.01% power conversion efficiency (PCE), whereas PbSe QD photovoltaics lag behind at 8.2% PCE. One reason for this difference is that there has been significantly less work done on surface passivation of PbSe QDs. Here, the surface passivation of chlorinated PbSe QDs is optimized via a halide ion exchange treatment using mixed halide CsPb(Br/I)3 perovskite nanocrystals. Champion devices made from treated QDs achieved a PCE of 9.2%, V oc of 0.56 V, J sc of 25.7 mA cm −2, and fill factor of 64%. Average PCEs for optimized cells are 8.9%. Detailed physical characterizations including capacitance‐voltage ( C ‐ V ), V oc, and J sc as a function of light intensity, transient photovoltage, and photocurrent measurements are all carried out to investigate the mechanism of the improvement in the PCE and to understand the role of the mixed halide perovskites in providing superior surface passivation for PbSe solar cells. At this time, 9.2% is the highest PCE yet reported for PbSe QDs solar cells. Abstract : The chloride coated‐PbSe quantum dots are passivated using CsPbX3 (X = Br and I) perovskite quantum dots via halide ion exchange in solution. Solar cells using PbSe quantum dots passivated by CsPbBr0.5 I2.5 mixed halide perovskites achieve a 9.2% power conversion, the highest reported efficiency for a PbSe QD device to date.